2020
DOI: 10.1186/s12896-020-00656-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of axenic cyanobacterium and the promoting effect of associated bacterium on axenic cyanobacterium

Abstract: Background Harmful cyanobacterial blooms have attracted wide attention all over the world as they cause water quality deterioration and ecosystem health issues. Microcystis aeruginosa associated with a large number of bacteria is one of the most common and widespread bloom-forming cyanobacteria that secret toxins. These associated bacteria are considered to benefit from organic substrates released by the cyanobacterium. In order to avoid the influence of associated heterotrophic bacteria on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…For E. coli a weak growth inhibition could be observed when cultivated in minimal medium, but not in complex medium ( Supplementary Figure 3 ). It might be possible that some heterotrophic bacteria are able to metabolize 7dSh, as it is reported that the cocultivation of cyanobacteria with heterotrophic bacteria can support the growth of the cyanobacteria ( Zheng et al, 2018 ; Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For E. coli a weak growth inhibition could be observed when cultivated in minimal medium, but not in complex medium ( Supplementary Figure 3 ). It might be possible that some heterotrophic bacteria are able to metabolize 7dSh, as it is reported that the cocultivation of cyanobacteria with heterotrophic bacteria can support the growth of the cyanobacteria ( Zheng et al, 2018 ; Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of agar concentration, plating method, and additions of reactive oxygen species scavengers on cyanobacterial growth on solid media Cyanobacterial cultivation and the generation of mutants are challenging due to their slower growth rate (Hayashi et al, 2011;Burnap, 2015;Gao et al, 2020). A very concentrated inoculum is required to grow cyanobacteria on a solid medium.…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors controlling the generation of fully segregated mutants, which include cyanobacterial strain background, lab conditions, and types of mutations ( Lea-Smith et al, 2016 ). Compared to heterotrophic bacteria, the growth rate of cyanobacteria is slow ( Burnap, 2015 ; Jaiswal et al, 2022 ), especially in solid medium ( Hayashi et al, 2011 ; Gao et al, 2020 ), which further confers a challenge for cyanobacterial transformation. Previous studies have tried to determine the optimum conditions for the growth of multiple cyanobacteria on solid media.…”
Section: Introductionmentioning
confidence: 99%
“…Filaments accumulate into a mucilaginous matrix rich in a complex polysaccharide enclosed by an outer envelope in Nostoc species capable of forming macrocolony. Nostoc macrocolonies can be observed as sheet-like or spherical forms with green to brown colorations, depending upon the species, dehydration state, and local environment [17][18][19][20][21][22]32]. In natural environments, macrocolonies of filamentous diazotrophic Nostoc are colonized by diverse microorganisms involved in biogeochemical cycles and ecosystem services [33].…”
Section: Discussionmentioning
confidence: 99%
“…The natural life cycle of primary producers may involve mutualistic, antagonistic, or commensal interactions with cyanophages, fungi, and heterotrophic bacteria. Positive or negative outcomes from such interactions have been previously discussed in Nostoc macrocolonies [18,19] and reported in Andean Nostoc macrocolonies [20][21][22]. However, studies on identifying members of the bacterial community associated with edible Llayta macrocolonies have been a pending issue.…”
Section: Introductionmentioning
confidence: 96%